428 The Lumbar Tap Trial Experience: An Analysis of Outcomes in 133 Adult Normal Pressure Hydrocephalus Patients Undergoing 2-Day Lumbar Tap Trial at a Single Center. (1st April 2022) - Cunningham, Coby; Leonardo, Jody
Abstract : INTRODUCTION: Lumbar Tap Trial (LTT) with high volume cerebrospinal fluid (CSF) removal is one of the primary adjunct testing modalities at a neurosurgeon's disposal in the diagnosis of normal pressure hydrocephalus (NPH). Patients responsive to LTT may receive permanent fluid diversion by way of shunt placement. METHODS: Retrospective review of the electronic medical records of 133 patients that underwent a 2-day LTT by a single surgeon at our adult hydrocephalus center was conducted. Each patient has been closely followed at our hydrocephalus clinic from the time of symptomatic presentation through LTT, eventual shunt placement (if performed), and frequent post-operative assessments. Assessment of improvement during LTT and following shunt placement includes a timed 25 ft. walk test at our clinic. RESULTS: From 2016 – present, 133 patients have undergone 136 completed LTTs. During initial LTT, no major complications such as death, infection, hemorrhage, or nerve-root injury were seen. Minor complications included post-tap low back pain, headache, and transient nerve-root irritation. Average improvement during timed 25 ft. walk test was 6.6 sec following LTT. Average improvement in timed walk test in patients receiving shunt placement was 13.9 sec compared to post LTT walk time. CONCLUSION: In patients with suspected NPH, high-volume LTT was found to be an effective and safe diagnostic tool in our patient population. Patients demonstrating significant objective improvement during a timed walk test are frequently recommended for shunting. Patients undergoing shunt placement following improvement on LTT continued to improve with a mean decrease in walk time post-operatively, highlighting the effectiveness of LTT in predicting symptomatic response to shunt placement.